UNDERSTANDING OUR FATHER IN THE CONTEXT OF HUMAN PERFECTION PREACHED IN THE SERMON ON THE MOUNT, ACCORDING TO ST. GREGORY OF NYSSA’S HOMILIES ON THE LORD’S PRAYER - PODARU, Adrian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2019)
It is not by chance that the prayer Our Father is recommended by Jesus Christ during the so-called Sermon on the Mount. All that has been said in this Sermon aimed at perfection: Be perfect, therefore, as your heavenly Father is perfect (Matt. 5, 48). Viewed in this light, the Lord’s prayer is also the prayer which is properly uttered only in a state of perfection, and even if it may be used as a mean to achieve perfection, nevertheless it is perfectly uttered only in a state of perfection; therefore, in a way, the Lord’s prayer is the aim of the Christian life. This is the view of St. Gregory of Nyssa and this is what this article tries to argue by using the texts of this Cappadocian Father.